Isolated Soy Protein Supplementation Combined With Resistance Training Improves Muscle Strength, Mass, and Physical Performance of Aging Female Mice - Lee, Mon-Chien; Hsu, Yi-Ju; Wu, Fang-Yu; Huang, Chi-Chang; Li, Hsueh-Yu; Chen, Wen-Chyuan (Frontiers in Physiology, 2022)
Background/Purpose: In recent years, the aging population has gradually increased, and the aging process is accompanied by health associated problems, such as loss of muscle mass and weakness. Therefore, it is important to explore alternative strategies on improving the health status and physical fitness of aged population. In this study, we investigated the effect of soy protein supplementation combined with resistance training on changes in muscle mass, muscle strength and functional activity performance of aging mice. Methods: Female Institute of Cancer Research (ICR) mice were divided into four groups (n = 8 per group), including sedentary control (SC), isolated soy protein (ISP) supplementation, resistance training (RT) and combination of ISP and RT (ISP+RT). Mice in designated groups received oral ISP supplementation (0.123g/kg/day), RT (5 days/week for a period of 4 week) or combination of both ISP plus RT for 4 weeks. Afterwards, we assessed muscle strength, endurance, and anaerobic endurance performance, and analyzed blood biochemical and pathological tissue sections to investigate whether there were adverse effects or not in mice. Results: We found that ISP supplementation effectively improved muscle mass, muscle endurance and endurance performance of aging female mice. The RT group not only showed similar results with ISP, but also increased muscle strength and glycogen content. Nevertheless, the combination of ISP supplementation and RT had greater beneficial effects on muscle strength, physical performance, glycogen levels, (p<0.05). In addition, the combination of ISP supplementation and RT had significantly increase type II muscle percentage and cross section area (p<0.05). Conclusions: Although ISP or RT alone improved muscle mass and performance, combination of ISP with RT showed greater beneficial effects in aging mice. Our findings suggest that regular exercise along with protein supplementation could be an effective strategy to improve overall health and physical fitness among elderly.